2013
DOI: 10.1155/2013/468624
|View full text |Cite
|
Sign up to set email alerts
|

Studying Close Approaches for a Cloud of Particles Considering Atmospheric Drag

Abstract: The present paper has the goal of studying close approaches between a planet and a group of particles. The mathematical model includes the presence of the atmosphere of the planet. This cloud is assumed to be created by the passage of the spacecraft in the atmosphere of the planet, which can cause the explosion of the spacecraft. The system is assumed to be formed by the Sun, the planet, and the spacecraft that explodes and becomes a cloud of particles. The Sun and the planet are assumed to be in circular orbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Recent examples of missions using Swing-Bys are Messenger and BepiColombo, both of them having the planet Mercury as a target (see McNutt et al [30,31], Grard [32] and Jehn et al [33]). There are also studies considering clouds of particles, instead of a single particle, as shown in references [34][35][36].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent examples of missions using Swing-Bys are Messenger and BepiColombo, both of them having the planet Mercury as a target (see McNutt et al [30,31], Grard [32] and Jehn et al [33]). There are also studies considering clouds of particles, instead of a single particle, as shown in references [34][35][36].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature is very reach in topics related to this field, starting from basic impulsive maneuvers (Roth 1967;Prussing 1970Prussing , 1969Eckel 1963;Hohmann 1925;Smith 1959;Bender 1962;Jin and Melton 1991;Jezewski and Mittleman 1982;Hoelker and Silber Hoelker and Silber;Shternfeld 1959;Gross and Prussing 1974;Eckel 1982;Prussing and Chiu 1986;Ting 1960;Walton et al 1975). Then, it goes to orbital maneuvers based in low thrust (Casalino and Colasurdo 2002;Casalino et al 1999;Brophy and Noca 1998;Zee 1963;Lion and Handelsman 1968;Prado 2007, 2008;Macau 2000;Macau and Grebogi 2006), swing-by techniques (Flandro 1966;Marsh 1988;Farquhard and Dunham 1981;Prado and Broucke 1995;Prado 2007;Gomes et al 2013;DeMelo et al 2009), and even gravitational capture (Belbruno and Miller 1993;Pierson and Kluever 1994;Neto and Prado 1998). It covers also some more applied concepts, like searches for specific orbits (Chiaradia et al 2003;Carvalho et al 2010;Araujo et al 2012;Domingos et al 2008;D'Amario et al 1982;Farquhar et al 1985;…”
mentioning
confidence: 99%